An empirical research based on spatial-temporal evolution of high-quality tourism development in Fujian Province of China. - Ying Ke; Min Yang; Yajun Xie (PLoS ONE)
The high-quality development of tourism is crucial to the sustainable development of regional economy. To evaluate high-quality tourism development, this paper has developed an index system with 6 second-level indicators and 24 third-level indicators and used methods of entropy-weight, AHP, and TOPSIS to empirically assess the high-quality tourism development of 9 cities in Fujian Province. According to the results, there are obvious regional differences in the development of high-quality tourism in Fujian Province. From 2016 to 2019, the overall development trend of cities in Fujian Province was consistent, showing a steady upward trend. Green development in tourism has the best performance, which was less affected by the COVID-19. Fuzhou and Xiamen contribute most to the tourism development of Fujian Province, while other cities are lagging behind for various reasons and the lack of innovation and shared development are two of them. Based on the results of the research, we put forward the following suggestions: Fujian should coordinate the planning of the province's green eco-tourism resources to maximize the use of resources. It should combine the advantages of the primary, secondary and tertiary industries and fully develop both advanced regions and under-developed regions. It should also explore areas of potential growth in the tourism sector, such as Sanming, Longyan, and Nanpin, by strengthening digital innovation and sharing resources with Xiamen, Fuzhou, Quanzhou and other highly-developed tourism regions.